CT‐guided stereotactic targeting accuracy of osteoid osteoma. Issue 3 (27th April 2012) - Widmann, Gerlig; Schullian, Peter; Fasser, Martin; Niederwanger, Christian; Bale, Reto
Abstract: Background: The aim of this study was to evaluate the CT‐guided stereotactic targeting accuracy for radiofrequency ablation of osteoid osteoma (OO), a small, benign but painful osseous lesion. Methods: Patient and extremity were fixed in a vacuum cushion. The OO was targeted using an optical navigation system with a stereotactic targeting device. For evaluation of targeting errors, the control CT with the needle in place was fused with the planning CT. Results: In 16 consecutive patients, nine OOs in the femur, four in the tibia, one in the spine, one in the ulna and one in the pubic bone were successfully targeted without complications. The mean ± SD lateral targeting error was 2.6 ± 1.7 mm at the needle entry and 1.9 ± 1.2 mm at the needle tip, and the mean angular error was 2.0 ± 1.3°. Conclusion: Stereotaxy allows for accurate and safe targeting of OOs in various bone regions. Copyright © 2012 John Wiley & Sons, Ltd.